Employee perception of CSR activities, job attachment and organizational commitment - Musa, Ummu Asma'; Abd Rahman, Azmawani (Universiti Putra Malaysia Press, 2015)
The idea that a business has duties toward society and its stakeholders is widely acknowledged and has increased dramatically in the recent years. This study examined the mediation effect of job attachment on the relationship between employee perception on corporate social responsibility CSR activities and organisational commitment. Data were obtained through survey questionnaires from a sample of 143 firms operating in Malaysia. The results indicated significant relationships between perception of CSR and job attachment, and between job attachment and organisational commitments. However, this study found no mediation effect of job attachment on the relationships between perception of CSR activities and organisational commitment. This indicates that CSR activities can directly affect both job attachment and relate to individual feelings toward the job and organisational commitment, which relate to feelings towards the organization. These results suggest that CSR activities make a powerful contribution to intangible organizational benefits. The study offers implications for both theory and practice.